2014
DOI: 10.2514/1.b35170
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray of 1-Butyl-3-Methylimidazolium Dicyanamide Under Variable Flow Rate Operations

Abstract: This report is published in the interest of scientific and technical information exchange, and its publication does not constitute the Government's approval or disapproval of its ideas or findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…The electrospray source in both setups was identical and has been described in previous works. [10,11] The source was simply the pairing of an extractor plate with a 1.5 mm diameter aperture and a conductive emitter (i.e. metalcoated fused-silica capillary at 50 µm diameter) set approximately 1.5 mm apart.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The electrospray source in both setups was identical and has been described in previous works. [10,11] The source was simply the pairing of an extractor plate with a 1.5 mm diameter aperture and a conductive emitter (i.e. metalcoated fused-silica capillary at 50 µm diameter) set approximately 1.5 mm apart.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported on the effects of volumetric flow rate on the emitted ion species from a capillary-style emitter employing the ionic liquid BMI-DCA (1-butyl-3methylimidazolium dicyanamide). [10,11] At the lowest flow rates sampled, the smallest ion species appeared to be the most intense as measured through quadrupole mass spectrometry with an upper m/q range of 1,000 amu/q. As the flow rate was increased, the presence of larger ion clusters such as the n = 3, 4, and 5 cations (i.e.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Miller et al reported absolute emission currents of a 1-butyl-3-methylimidazolium dicyanamide (BMIM-DCA) capillary electrospray at 589, 772, and 1032 nA for flowrates 0.46, 0.82, 1.29 nl/s. 7 The increase in BMIM-DCA emission current compared to EMIM-NTf2 at similar flowrates is the result of the increase in conductivity, from 0.92 to 1.052 S/m, surface tension, from 35.7 mN/m to 48.6 mN/m, and a decrease in electrical permittivity, from 12.3 to 11.3. The ILFF solutions used in Exp-1 and Exp-2 also have different fluid and electrical properties than its neat IL carrier fluid.…”
Section: A Effects Of Nanoparticle Concentrationmentioning
confidence: 94%
“…[93,[100][101][102][103]. Liquid metals like cesium, gallium and indium have also been used as propellants due to their high atomic mass and a low ionization potential [104].…”
Section: Design Considerations and Technologiesmentioning
confidence: 99%